Analisi Efektivitas Pengendalian Internal terhadap Mitigasi Risiko Kecurangan dalam Pengelolaan Keuangan Daerah (Studi Kasus BPKD Kabupaten Gowa) - sitti Aliyah; Ismail Rasulong; Asriani Hasan (Jurnal Riset Akuntansi Politala, 2026)
This study is motivated by the high risk of fraud in local government financial management, which remains a significant issue in the public sector. Weak internal control implementation, limited effectiveness of internal audit, and low anti-fraud awareness may create opportunities for financial misconduct. This research aims to analyze the effectiveness of internal control in mitigating fraud risk in local financial management at the Regional Financial Management Agency (BPKD) of Gowa Regency, as well as to examine the role of internal audit and anti-fraud awareness in supporting the internal control system. The study employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. Key informants include officials and staff directly involved in financial management and oversight processes. The findings indicate that internal control at BPKD Gowa Regency has been implemented in accordance with existing regulations; however, its effectiveness has not been fully optimized due to limitations in human resources, inconsistencies in procedural implementation, and high workload pressures. Internal audit and anti-fraud awareness play a crucial role in strengthening internal control and reducing fraud risk. This study concludes that strong synergy among internal control, internal audit, and anti-fraud awareness is essential to enhance accountability, transparency, and integrity in local government financial management.